Efecto del tiempo de escaldado y fajilla termoformable sobre el pardeamiento de salsa picante del tomate de árbol (cyphomandra betacea cav) - Conforme Ozaeta, Gema Gabriela (2019)
The objective of this investigation was to evaluate the effect of thermoformable blanching time and faber on the tanning of spicy tomato sauce (Cyphomandra betacea Cav). Experimental research was carried out in which 6 study treatments were implemented. For the organoleptic characteristics Scoring Test was applied. The scalding time, the covering with a cloth and the interaction of both did not differ on the variables Brix and pH, both on day 1 and day 60; while the acidity and the consistency did have significant differences on day 60. As for the color the luminosity was affected, the red and yellow color on the 60th days at the time of scalding and the interaction of blanched time / covering with cloth and without it. The proposed times had no influence on control of the scalded of the hot sauce with tomato tree and the covering with the thermoformable cloth did not counteract the oxidation that takes place in the hot sauce. The product evaluated with 4 minutes of blanching and covering with thermoformable cloth was the one that presented the highest degree of acceptability on the part of the untrained panelists with the organoleptic attributes evaluated. It is concluded that the browning of the hot sauce with tomato tree is not influenced by the scalding times and the thermoformable coating with organoleptically, the best spicy sauce with tomato tree for the untrained panelists was T5 (4 minutes of blanching) and covering with thermoformable cloth).